2002
DOI: 10.1080/09603120120110040
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination of Japanese households and related concern about sanitation

Abstract: The bacterial contamination of Japanese homes and the attitudes of Japanese people toward sanitation were studied. By taking bacterial counts of approximately 90 places each in five homes, this study found kitchens to have the greatest degree of bacterial contamination, followed by bathing rooms. Toilets had less bacterial contamination than was expected. While concern about bacteria on highly contaminated items such as sponges, towels for wiping counters, and other reservoirs/disseminators was common, there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 5 publications
5
38
2
Order By: Relevance
“…This is higher than some previous reported detections, e.g. 5% (Scott et al, 1982), but lower than the 20% reported by Ojima et al (2002), or the 27.4% reported by Spiers et al (1995). Considering such detection frequencies, it is good that the intoxication caused by this pathogen is usually relatively mild and rapidly self-limiting, to the extent that the majority of cases of staphylococcal food intoxication go unreported.…”
Section: Isolation Of Speciwc Food Pathogenscontrasting
confidence: 53%
“…This is higher than some previous reported detections, e.g. 5% (Scott et al, 1982), but lower than the 20% reported by Ojima et al (2002), or the 27.4% reported by Spiers et al (1995). Considering such detection frequencies, it is good that the intoxication caused by this pathogen is usually relatively mild and rapidly self-limiting, to the extent that the majority of cases of staphylococcal food intoxication go unreported.…”
Section: Isolation Of Speciwc Food Pathogenscontrasting
confidence: 53%
“…Ojima et al [16] Regnath et al [17] and Schelstraete et al [18] focused on the interior (primarily bathrooms/washrooms and kitchens) of CF patient homes. In an earlier study, we examined a large number of outdoor and indoor sites, but only in homes without CF patients [19].…”
mentioning
confidence: 98%
“…Although fecal contamination in playground sandpits by dogs and cats (Fujisawa et al, 1995) and distributions of microorganisms in households (Ojima et al, 2002a;Ojima et al, 2002b) has been dissussed, the matters above were not described in those reports.…”
Section: Introductionmentioning
confidence: 86%